Pengaruh Pertumbuhan Laba, Investment Opportunity Set dan Good Corporate Governance Terhadap Kualitas Laba Pada Perusahaan Sub Farmasi Yang Terdaftar di Bursa Efek Indonesia - Andika Hasburrahman (Universitas 45 Surabaya, 2024)
This research aims to examine the influence of profit growth, investment opportunity set and good corporate governance on earnings quality. This research uses multiple linear regression as a data analysis technique assisted by SPSS with the sample criteria being sub-pharmaceutical financial reports listed on the Indonesian stock exchange in 2018-2023. Based on these criteria, a sample of 10 companies was obtained over a 6 year financial reporting period. The research results show that profit growth (X1) does not have a significant effect on profit quality. Investment Opportunity Set (X2) has a positive and significant effect on earnings quality. Good Corporate Governance (X3) has no effect on quality